Pengembangan Game “Mythics.Apk” untuk Melatihkan Kemampuan Berfikir Tingkat Tinggi Siswa SMP - Sahal, M. Abdulloh; Kurniawan, Agus Prasetyo; Lubab, Ahmad (Supermat : Jurnal Pendidikan Matematika, 2023)
Higher order thinking skills are needed in learning mathematics. Teachers can encourage students to practice higher order thinking skills through six stages, namely 1) seeking information; 2) submit allegations; 3) conduct an inquiry; 4) make a conjecture; 5) looking for alternatives; 6) draw conclusions. These six stages are very likely to be inserted into RPG-type game content to make it more interesting and increase student learning motivation. The research method used is the development with the Plomp model which consists of a preliminary research phase, a prototyping phase and an assessment phase. The learning media developed in this study is an android game with the title MYTHICS. Data collection techniques used in the form of field notes and validation. The results showed that in the preliminary research phase a literature study and needs analysis was carried out. In the prototyping phase, the game map is made, the game character is created, the storyline is made, the android touch screen control buttons are made, the battle level and problem level are designed in the game, and music is added. Finally, the assessment phase "MYTHICS.apk" was declared valid from the validation results with an average total validation value of 3.785 and was declared practical based on the validator's assessment, where two validators stated that the media could be used without revision and the other two stated that the media could be used with slight revisions.